Dropped Gallstone Presenting as Recurrent Abdominal Wall Abscess - Kaushik Kumar, MD; Christopher J. Haas, MD, PhD (Radiology Case Reports, 2022)
Dropped gallstones are a known complication of laparoscopic cholecystectomy. Rarely, dropped stones may be embedded within the potential intraperitoneal spaces or abdominal wall, mimicking metastatic implants, tuberculosis, peritoneal loose body, actinomyces, and primary tumors, which when coupled with the fact that most bile stones are radiolucent, leads to diagnostic challenges. Here, we report a case of abdominal wall abscess due to a dropped stone that presented over 15 years after laparoscopic cholecystectomy. An 86-year-old male with laparoscopic cholecystectomy for management of acute cholecystitis complicated by post-cholecystectomy choledocholithiasis over 15 years back presented to the emergency department with intermittent, asymmetric abdominal “bulging” and a reported 16-pound weight loss of 3 months duration. He remained hemodynamically stable and physical examination demonstrated approximately 9 cm × 7 cm, nontender and slightly fluctuant mass appreciable on the right lateral abdominal wall extending to the right flank. Laboratory revealed leukocytosis and elevated lactic acid. Abdominal ultrasound and abdominal computed tomography demonstrated a 10.6 × 7 × 16 cm cystic mass with echogenic debris adjacent to the anterior segment of the right hepatic lobe. The patient presented multiple times with re-accumulation. A drain was subsequently placed and antibiotic therapy initiated with subsequent resolution. Follow-up magnetic resonance imaging revealed a punctate calcification within the abscess pocket. Retained stones should be considered in the differentials of patients presenting with abdominal discomfort and abdominal “masses.” The clinical suspicion must remain high secondary to the potential temporally prolonged presentation, indolent nature of inflammation, and unusual sites of physical manifestations.